EFL STUDENTS'ABILITY IN PERFORMING AUTONOMOUS LEARNING AND THEIR WRITING PROFICIENCY ACROSS COGNITIVE STYLES - Dyah Dewi Masita (Pascasarjana Universitas Negeri Malang, 2016)
This study is intended do investigate the relationship between students' autonomy and their writing proficiency across cognitive styles. Correlational research design was fit to understand the relationship between two continuous variables. To obtain the required data, Writing Autonomy Questionnaire, and writing test was administered to 155 students of sixth semester from two private colleges at Malang. The result presented that there is significant and positive correlation between those variables (r = .437). Meanwhile variables pressented gave contribution to the other variable due to its correlationship. Penelitian ini bertujuan untuk mengetahui hubungan antara autonomy mahasiswa dan kemampuan menulis mereka berdasarkan gaya berpikir. Metode penelitian yang sesuai adalah korelasi untiuk memahami hubungan dua variabel. Writing Autonomy Questionnaire, dan tes menulis disebarkan kepada 155 siswa semester 6 untuk memperoleh data yang diperlukan. Hasil peneliatian ini menunjukkan bahwa ada hubungan positif dan signifikan antara kedua variabel tersebut (r = .437). Sementara itu variabel yang teridentifikasi tersebut saling berkontribusi dikarenakan hasil analisa yang menunjukkan hubungan positif dan signifikan.